2003
DOI: 10.1136/heart.89.4.427
|View full text |Cite
|
Sign up to set email alerts
|

Coronary surgery with non-cardioplegic methods in patients with advanced left ventricular dysfunction: immediate and long term results

Abstract: Objective: To evaluate perioperative results and long term survival in patients with severe left ventricular (LV) dysfunction undergoing coronary artery bypass grafting (CABG) using non-cardioplegic methods. Methods: From April 1990 through December 1999, 4100 consecutive patients underwent isolated CABG using hypothermic ventricular fibrillation. Of these, 141 (3.4%) had severe LV dysfunction (ejection fraction < 30%). Mean age was 58.3 (9.6) years. 64 patients (45.4%) were in Canadian Cardiovascular Society … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 25 publications
3
12
0
Order By: Relevance
“…Magee et al 23 demonstrated CPB in their study as a predictor of in-hospital mortality in patients who underwent CABG. Antunes et al 24 in their study showed that perfusion time is longer in patients with left ventricular dysfunction. Perfusion time in our study was longer in patients with EF≤35% compared with those without, and in this study we actuated perfusion time (OR=1.014, CI=1.006 to 1.027) as a predictor of mortality in patients with EF≤35%.…”
Section: Discussionmentioning
confidence: 92%
“…Magee et al 23 demonstrated CPB in their study as a predictor of in-hospital mortality in patients who underwent CABG. Antunes et al 24 in their study showed that perfusion time is longer in patients with left ventricular dysfunction. Perfusion time in our study was longer in patients with EF≤35% compared with those without, and in this study we actuated perfusion time (OR=1.014, CI=1.006 to 1.027) as a predictor of mortality in patients with EF≤35%.…”
Section: Discussionmentioning
confidence: 92%
“…In a group of 141 consecutive cases with EF less than 30% (12%-29%), submitted to isolated coronary surgery using noncardioplegic techniques, we [19] observed a 2.8% hospital mortality and an actuarial survival of 96% and 86% at 1 and 5 years, respectively. In the immediate postoperative period, less than 35% of the patients required inotropic support for over 24 hours, and aortic counterpulsation was used in only 3.5%.…”
Section: Coronary Bypass Surgerymentioning
confidence: 89%
“…Although the experimental results are inspiring [40][41][42], clinical results have yet not been made available and trials are still being carried out. [3] 0.24 0 74 Mitral insufficiency Calafiore et al [11] 0.27 4.1 78 Gummert et al [12] 0.25 6.1 86 66 Bishay et al [13] 0.28 2.3 88 72 Rothemburger et al [15] 0.23 91 77 Coronary bypass Antunes et al [19] ? …”
Section: Other Surgical Optionsmentioning
confidence: 98%
“…26 Within the last decade mortality rates under 5% are common. 3,7,13,[26][27][28][29] Differences in surgical series may reflect patient selection. 30,31 Nevertheless, the incidence of perioperative myocardial injury is low (i.e.…”
Section: Currently the Management Of These Patients Lies Within A CLImentioning
confidence: 98%
“…<2%), in series with low mortality. 3,7,13,19,26,28 Hence, attention to myocardial protection is critical. There appears to be no significant difference between the different techniques of myocardial protection.…”
Section: Currently the Management Of These Patients Lies Within A CLImentioning
confidence: 99%